Comparison of optimisation based control techniques for the control of a CSTR. (1st January 2000) - Kittisupakorn, Paisan; Hussain, Mohamed Azlan
This paper presents the implementation of optimisation based control techniques an open loop optimal control (OLOC) and a receding horizon control (RHC), for the control of a continuous stirred tank reactor (CSTR) system with exothermic reactions, which exhibit multiple steady state conditions. This type of control techniques requires the solution of an open loop optimal control problem which consists of an objective function, system constraint and state or manipulated variable constraint. Simulation results have demonstrated that the OLOC controller can only perform well if all model parameters are known exactly and not when model mismatches exist. The RHC controller, on the other hand, gives better results and is much more robust for systems with plant/model mismatches within a certain range.